Penentuan Alternatif Material Part ABS Untuk Menjamin Kesinambungan Pasokan Pada Perusahaan Manufaktur Sepeda Motor - M. Yani Syafei; Tri Sutrisno (JIE Scientific Journal on Research and Application of Industrial System, 2021)
Ensuring the continuous supply of materials in the manufacturing system is a very important factor in ensuring the smooth production process and product fulfillment to consumers. A motorcycle manufacturing company that has several plastic parts injection suppliers, but the problem is that some plastic parts suppliers only take from one material supplier with the trademark ABS-J. This single supplier is very risky in terms of the ability to supply materials and also the possibility of a price monopoly that can be done by material suppliers because they have no competitors. With the PDCA approach, research is conducted to determine the addition of alternative ABS materials to ensure material supply availability and also obtain potential benefits that can be obtained by implementing multi-ABS material suppliers. With the trial and error method of using other alternative materials, namely ABS Star and also fish bone analysis, can get the same quality results as ordinary ABS-J material, by changing the injection machine parameter settings. The parameter setting is oriented towards reducing the temperature of the material by lowering the temperature of the barrel to (230-225-220-200 ° C), reducing the injection speed (45-55-45-35) and using Holding Pressure (70 Pa) for ABS Star material.